STUDY ON THE ANTIOXIDANT ACTIVITY DURING THE FORMULATION OF BIOLOGICAL ACTIVE INGREDIENT - Zsófia Edit Pápay; István Antal (European Scientific Journal, ESJ, 2014)
Background& Aims:This study examined the antioxidant activity of different extract of parsley (Petroselinum crispum) with DPPH method. This assay is one of the most commonly used because of its simplicity and efficiency. Parsley is a widely known culinary plant and herbal medicine in Europe since ancient times. It is easy to grow and many biological activities are attributed to the flavonoids in the leaf. Biological active herbal medicines have an advantage over drugs because they are safer and cheaper. Methods: The antioxidant activities of the main flavonoid and its glycosides were measured. With previously optimized extraction procedure, the effect of particle size and extraction temperature were tested regarding the radical scavenging activity and drug content with spectrophotometric and HPLC-UV method. The antioxidant capacity of the extracts for 7 days were also investigated. Results: The aglicon possesses bigger antioxidant activity over the glycosidic forms. The scavenging activity was decreased with smaller the particle size of the dried leaves and higher temperature, but the flavonoid content was increased. Conclusion: The use of medicinal plants in the therapy is emerging. The exact dose and mode of action of the medicinal plants are still an unfolding area therefore the study on the main mode of action - the antioxidant activity – influenced by the formulation is important.